2019
DOI: 10.1016/j.cgh.2018.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Parameters Correlate With Endoscopic Activity of Ulcerative Colitis: A Systematic Review

Abstract: BACKGROUND & AIMS: Optimal management of patients with ulcerative colitis (UC) requires assessment of disease activity-usually by endoscopy, which is invasive, costly, and not risk free. We performed a systematic review to determine whether clinical symptoms correlate with findings from endoscopy assessments of patients with UC. METHODS: We performed a systematic review of publication databases from January 1980 through July 2018 to identify clinical trials and observational studies reporting correlations amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 44 publications
(70 reference statements)
1
32
0
1
Order By: Relevance
“…Their importance in management has been recognised in the consensus guidelines that identify resolution of rectal bleeding and normalisation of stool frequency as treatment targets . Prior work has suggested that the majority of patients with complete resolution of rectal bleeding and normalisation of stool frequency achieve endoscopic improvement (MES 0/1); however, these studies did not evaluate several important factors that may influence endoscopic disease activity including classification of endoscopic remission (MES 0) vs improvement (MES 0 or 1), timing of assessment (post‐induction vs maintenance), evolution in scoring conventions regarding friability or the influences of central scoring of endoscopy. In a pooled analysis of individual participant data for over 2500 participants from pivotal ulcerative colitis clinical trial programs, we have made several important observations, which extend prior work in this arena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their importance in management has been recognised in the consensus guidelines that identify resolution of rectal bleeding and normalisation of stool frequency as treatment targets . Prior work has suggested that the majority of patients with complete resolution of rectal bleeding and normalisation of stool frequency achieve endoscopic improvement (MES 0/1); however, these studies did not evaluate several important factors that may influence endoscopic disease activity including classification of endoscopic remission (MES 0) vs improvement (MES 0 or 1), timing of assessment (post‐induction vs maintenance), evolution in scoring conventions regarding friability or the influences of central scoring of endoscopy. In a pooled analysis of individual participant data for over 2500 participants from pivotal ulcerative colitis clinical trial programs, we have made several important observations, which extend prior work in this arena.…”
Section: Discussionmentioning
confidence: 99%
“…In ulcerative colitis, the most commonly used patient‐reported outcomes are the rectal bleeding sub‐score (RBS) and stool frequency sub‐score (SFS) of the Mayo score . Two recent systematic reviews which evaluated the operating properties of the RBS and SFS for non‐invasive assessment of endoscopic inflammation concluded that normalisation of these assessments is strongly associated with the presence of endoscopic improvement (Mayo endoscopic sub‐score [MES] 0 or 1) which comprises both endoscopic remission (MES 0) and mildly active disease (MES 1) . Notwithstanding that these reviews underscored the importance of patient‐reported outcome assessment in ulcerative colitis, several limitations remain in our understanding of the relationships between patient‐reported outcomes and endoscopy that warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…These findings could indicate that dose intensification is perhaps more effective for UC than CD but is more likely due to the operating characteristics of the clinical disease activity indices involved. The low baseline HBI in several patients despite objective evidence of active disease is indicative of the fact that clinical disease activity indices used for CD (ie, HBI and Crohn's disease activity index (CDAI)) correlate less well with disease activity than those used for UC 25 26…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms often correlate poorly with the endoscopically defined disease in patients with CD, making it challenging to monitor the disease. To some extent, this also applies to UC 3 4. Furthermore, Narula et al in a systemic review and meta-analysis described that many patients still had an abnormal stool frequency despite endoscopic remission 5…”
Section: Introductionmentioning
confidence: 99%